Optimizing the Utilization of the Portal Rumah Belajar as a Learning Management System in Digital Learning: A Literature Review - Zen, Zelhendri; Waty, Dira Febria; Yenira, Fitria; Aziz, Luthfi Afdil; Yuarsa, Rufina Agustin; Setiawati, Setiawati; Yudiana, Yudiana (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
The transformation of digital learning in Indonesia necessitates the pedagogically integrated use of Learning Management Systems (LMS). Portal Rumah Belajar is a national LMS developed by the government to support digital learning in alignment with the national curriculum. This study aims to systematically examine the utilization of Portal Rumah Belajar as an LMS in the context of formal education through a literature review approach. Data were collected from journal articles, books, research reports, and official documents published between 2015 and 2025 and analyzed using content analysis techniques. The primary referenes used onsist of 15 articlesthat intensively examine the Portal Rumah Beljar. The findings indicate that Portal Rumah Belajar has the potential to enhance access to digital learning resources, support self-directed learning, and facilitate interaction and learning assessment. However, its utilization has not been fully optimized due to limitations in teachers’ digital pedagogical competence and insufficient integration of the platform into instructional planning. Therefore, optimizing Portal Rumah Belajar requires strengthening pedagogical design, institutional support, and sustainable utilization of its features.